Assessment of the gut microbiota of children with obstructive sleep apnea syndrome: A systematic review - da Silva, Livia Maria Alves Valentim [UNESP]; Assunção, Wirley Gonçalves [UNESP]; Bento, Victor Augusto Alves [UNESP]; Sachi, Victor Perinazzo [UNESP]; Colombo, Fabio Eduardo [UNESP]; Ique, Manuel Martin Adriazola [UNESP]; Faria, Bianca Martinatti Andrade [UNESP]; Bertoz, André Pinheiro de Magalhães [UNESP] (Elsevier, 2024)
Sleep-disordered breathing promotes not only unfavorable craniofacial changes in untreated pediatric patients but also neurocognitive, metabolic, cardiovascular, and even long-term social alterations. This systematic review evaluated whether children diagnosed with obstructive sleep apnea syndrome (OSAS) have different intestinal microbiota constitutions from healthy children and was based on the PRISMA guidelines (PROSPERO: CRD42022360074). A total of 1562 clinical studies published between 2019 and 2023 were selected from the PubMed/MEDLINE, Embase, Web of Science, Scopus, and Cochrane Library databases, of which five were included in the qualitative analysis, three being randomized and two prospective. The methodological quality was assessed (RoB 2.0 and ROBINS-I) and all studies showed a negative effect of intervention. Sleep deprivation and intermittent hypoxia in children with OSAS seem to trigger a cascade of inflammatory pathways that exacerbate the tissue response to the release of reactive oxygen species and the generation of oxidative stress, leading to a reduction in oxygen supply to the intestinal mucosa and the integral destruction of the intestinal barrier. More evidence-based investigations are needed to optimize the identification of possible alterations in the gut microbiota of pediatric patients, given that its composition may be influenced by the patient's sleep quality and, consequently, by OSAS, showing quantitative and qualitative alterations compared to that found in healthy individuals.
Keywords: Dysbiosis. gut microbiota. sleep. sleep disordered breathing. pediatric obstructive sleep apnea